2021
DOI: 10.1126/sciadv.abe0997
|View full text |Cite
|
Sign up to set email alerts
|

Falling living standards during the COVID-19 crisis: Quantitative evidence from nine developing countries

Abstract: Despite numerous journalistic accounts, systematic quantitative evidence on economic conditions during the ongoing COVID-19 pandemic remains scarce for most low- and middle-income countries, partly due to limitations of official economic statistics in environments with large informal sectors and subsistence agriculture. We assemble evidence from over 30,000 respondents in 16 original household surveys from nine countries in Africa (Burkina Faso, Ghana, Kenya, Rwanda, Sierra Leone), Asia (Bangladesh, Nepal, Phi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
365
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 369 publications
(391 citation statements)
references
References 25 publications
22
365
0
4
Order By: Relevance
“…It is clear from the results that the pandemic has had substantial effects on income within the working equid community ( Table 2 ). Decreases in income for those living in LMICs attributed to the pandemic have been reported in other studies [ 37 , 38 ]. For example, Egger et al (2021) reported that, across nine developing countries, a median of 68% respondents had experienced a reduction in income [ 37 ].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It is clear from the results that the pandemic has had substantial effects on income within the working equid community ( Table 2 ). Decreases in income for those living in LMICs attributed to the pandemic have been reported in other studies [ 37 , 38 ]. For example, Egger et al (2021) reported that, across nine developing countries, a median of 68% respondents had experienced a reduction in income [ 37 ].…”
Section: Discussionsupporting
confidence: 69%
“…Decreases in income for those living in LMICs attributed to the pandemic have been reported in other studies [ 37 , 38 ]. For example, Egger et al (2021) reported that, across nine developing countries, a median of 68% respondents had experienced a reduction in income [ 37 ]. The World Bank has made grim predictions: “In the two decades since 1999, the number of people living in extreme poverty worldwide has fallen by more than one billion people.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We gratefully acknowledge the enormous efforts of all the call center agents at the three study sites who worked intensively throughout the COVID-19 epidemic and the participants who responded multiple times despite the difficult social and economic conditions. Core surveillance activities, including the telephonic surveillance of COVID- 19…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Robust data are essential for evaluating the hypotheses that lockdowns cause substantial harm or are futile and for targeting locations that are the most in need of resources. The impact of NPIs has been evaluated in various low-and middle-income countries, generating evidence of early reductions in income and food security and the rapid, substantial uptake of protective behaviors [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%